A new approach to deposit homogeneous samples of asbestos fibres for toxicological tests in vitro - Della Ventura, Giancarlo; Rabiee, Ahmad; Marcelli, Augusto; Macis, Salvatore; D’Arco, Annalisa; Iezzi, Gianluca; Radica, Francesco; Lucci, Federico (Frontiers in Chemistry, 2023)
In this paper we describe the results obtained with a novel method to prepare depositions of asbestos fibres for toxicological tests in vitro. The technique is based on a micro-dispenser, working as an inkjet printer, able to deposit micro-sized droplets from a suspension of fibres in a liquid medium; we used here a highly evaporating liquid (ethanol) to reduce the experimental time, however other solvents could be used. Both the amount and spatial distribution of fibres on the substrate can be controlled by adjusting the parameters of the micro-dispenser such as deposition area, deposition time, uniformity and volume of the deposited liquid. Statistical analysis of images obtained by optical and scanning electron microscopy shows that this technique produces an extremely homogeneous distribution of fibers. Specifically, the number of deposited single fibres is maximized (up to 20 times), a feature that is essential when performing viability tests where agglomerated or untangled fibrous particles need to be avoided.